A routine transition in the digital era? The rise of routine work in Central and Eastern Europe. (August 2017) - Keister, Roma; Lewandowski, Piotr
In this article, we study the shift from manual to cognitive work in 10 Central and Eastern European economies. While highlighting the growth in the non-routine cognitive component of jobs, we pay particular attention to the increase in routine cognitive tasks, a trend distinguishing Central and Eastern European economies from the most advanced economies. We find that in all countries routine cognitive tasks were most common in the middle of wage distribution, but increasingly rare among the top earners. We identify two groups of workers whose jobs depend most on performing routine cognitive tasks: medium-skilled men in the manufacturing sectors and medium-skilled women in the service sectors, who jointly represent 33 per cent of Central and Eastern European workers. Should technological progress reduce demand for routine work in Central and Eastern Europe, a large proportion of workers would be affected and wage inequality would rise. We conclude with the policy implications of our findings.